Neurogeriatric approach to delirium/dementia in a multi‐faculty university hospital. Issue 1 (20th October 2020) - Sakakibara, Ryuji; Katsuragawa, Shuichi; Iimura, Ayako; Ogata, Tsuyoshi; Terayama, Keiichiro; Doi, Hirokazu; Suzuki, Keiko; Tateno, Fuyuki; Aiba, Yosuke; Sato, Megumi
Abstract: Objective: Delirium/dementia (collectively called cognitive spectrum disorder [CSD]) is a major issue in hospital wards. However, few reports are available on the incidence of CSD on multi‐faculty wards or on the factors contributing to it. The aim of this study was to address these issues by a neurogeriatric team (neurologists, psychiatrists, specialist nurses, and link nurses from all wards). Patients and Methods: This was a retrospective study with a 12‐month recruiting period, a prospective follow‐up period of 3.0 ± 2.5 weeks, and ≥1×/week visits. We diagnosed acute‐onset delirium by the Confusion Assessment Method and analyzed underlying conditions. We also diagnosed premorbid dementia by neurocognitive examination and neuroimaging following published criteria. Results: Our subjects were 723 CSD from 15 faculties, accounting for 6.5% of admissions, 393 men and 330 women, mean age 81 years. CSD was prevalent in cardiology/cardiac surgery (CAR), orthopedic surgery (OP), and neurology/neurosurgery (N), with dementia alone in ophthalmology and a combination of delirium/dementia in the other faculties. Premorbid dementia were diagnosed with Alzheimer's disease (AD), white matter disease, dementia with Lewy bodies (DLB), or some combination of these. Delirium was accompanied by worsening of gait difficulty. The ratio of brain (N) versus extra‐brain was 105 (14.5%):618 (85.5%). Severe CSD was common in DLB than AD but without statistical significance. Conclusion: Total 6.5% of hospital admissions showed CSD, with CAR, OP, and N being prevalent. The ratio of brain versus extra‐brain was 14.5%:85.5%. Severe CSD was more prevalent in DLB patients than in AD patients, but without statistical significance.